The Effect Of Online Promotions, Celebrity Endorsers And Prices On Online Buying Interest On Tiktok Shop (Study On Generation Z Users Of The Tiktok Application) - Mustari, Mustari; Putrawan, Muh. Rizah (International Journal of Education, Vocational and Social Science, 2024)
This research is a quantitative research that intends to reveal how online promotions, celebrity endorsers and prices affect online buying interest in tiktok shops. The research data was collected through filling out a questionnaire using a Google Form given to 31 respondents who used the TikTok application. The method used to analyze the data is multiple linear regression analysis. The results of the study show that 1) simultaneously online promotion, celebrity endorer and price have a significant effect on online buying interest. 2) partially shows that online promotion (X1) has a positive and significant effect on online buying interest (Y). This shows that the characteristics of online promotion have an important role in attracting online buying interest in Tiktok Shop. 3) celebrity endorsers (X2) do not have a positive and significant effect on online buying interest on Tiktok Shop (Y). This shows that the characteristics of celebrity endorsers have no influence on online buying interest on Tiktok Shop. 4) price (X3) has a positive and significant effect on online buying interest on Tiktok Shop (Y). This shows that price characteristics affect online buying interest on Tiktok Shop.